2010
DOI: 10.1521/aeap.2010.22.5.402
|View full text |Cite
|
Sign up to set email alerts
|

Preventing AIDS through Live Movement and Sound: Efficacy of a Theater-Based HIV Prevention Intervention Delivered to High-Risk Male Adolescents in Juvenile Justice Settings

Abstract: Male adolescents who cycle through the juvenile justice system are at high risk for HIV infection, yet there are few HIV prevention interventions for this high-risk population. This study evaluates the efficacy of Preventing AIDS through Live Movement and Sound (PALMS), an innovative, theory-based HIV risk reduction intervention that uses theatrical performances and role-play. The study used a nonrandomized concurrent comparison group design. A total of 289 predominantly African American males aged 12-18 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Some evidence indicates that talking about sexual behavior, in particular, having conversations about safe sex practices, can reduce sexual risk behavior. Increasing safe sex communication with partners has been a focus of several AIDS/HIV risk prevention programs that have included samples of incarcerated adolescents, although most have relied on nonrandomized designs with juvenile justice males (Lauby et al, 2010; Magura, Kang, & Shapiro, 1994) or have yet to demonstrate long-term effects (Marvel, Rowe, Colon-Perez, DiClemente, & Liddle, 2009; Swendeman & Rotheram-Borus, 2010; Woodson, Hives, & Sanders-Phillips, 2010). One promising approach that used a randomized clinical trial design with a sample of juvenile justice youths found that youths randomly assigned to the intervention condition reported more open conversations with their sex partners about HIV/AIDS and safe sex practices at a 6-month follow-up than did youths who were assigned to services as usual, with a moderate effect size (Marvel et al, 2010).…”
Section: Communication About Safer Sex As a Buffer Against Riskmentioning
confidence: 99%
“…Some evidence indicates that talking about sexual behavior, in particular, having conversations about safe sex practices, can reduce sexual risk behavior. Increasing safe sex communication with partners has been a focus of several AIDS/HIV risk prevention programs that have included samples of incarcerated adolescents, although most have relied on nonrandomized designs with juvenile justice males (Lauby et al, 2010; Magura, Kang, & Shapiro, 1994) or have yet to demonstrate long-term effects (Marvel, Rowe, Colon-Perez, DiClemente, & Liddle, 2009; Swendeman & Rotheram-Borus, 2010; Woodson, Hives, & Sanders-Phillips, 2010). One promising approach that used a randomized clinical trial design with a sample of juvenile justice youths found that youths randomly assigned to the intervention condition reported more open conversations with their sex partners about HIV/AIDS and safe sex practices at a 6-month follow-up than did youths who were assigned to services as usual, with a moderate effect size (Marvel et al, 2010).…”
Section: Communication About Safer Sex As a Buffer Against Riskmentioning
confidence: 99%
“…Results indicated significantly greater knowledge and intention to use birth control as well as increased willingness to discuss sexual topics with partners and parents after viewing the performance. A descriptive study by DiIorio and colleagues (2002) (Lauby et al, 2010). However, the usual audience for these theater interventions have traditionally been youth, not parents.…”
Section: Theater-based Interventionsmentioning
confidence: 99%
“…The CDC approach required all CBO evaluations to satisfy criteria for evaluation design and strength of evidence concerning evaluation outcomes to potentially qualify for inclusion in the Compendium of Evidence-Based HIV Behavioral Interventions (http://www.cdc.gov/hiv/prevention/research/compendium/rr/index.html), and for possible packaging through CDC’s Replicating Effective Interventions Plus project (http://www.cdc.gov/hiv/prevention/research/rep/packages) and dissemination for use by service provider organizations through CDC’s Diffusion of Effective Behavioral Interventions program (http://www.effectiveinterventions.org; Collins & Tomlinson, 2014). The Innovative Interventions Project funded People of Color in Crisis to evaluate the small-group Many Men, Many Voices (3MV) intervention, which the CBO had co-developed for and had been delivering to black MSM in the New York area since 1997 (Wilton et al, 2009); SisterLove, Inc. to evaluate the small-group Healthy Love Workshop intervention for heterosexual black women that it developed and had been delivering to women in metropolitan Atlanta since 1989 (Diallo et al, 2010); and the Philadelphia Health Management Corporation to evaluate the theater-based Preventing AIDS through Live Movement and Sound (PALMS) intervention for incarcerated and adjudicated minority adolescent males that it had developed and had been delivering to these populations since 1993 (Lauby et al, 2010). Based on the evaluation results and the rigor of the evaluation design, all of the CBO interventions satisfied CDC’s criteria for classification as evidence-based interventions.…”
Section: Methodsmentioning
confidence: 99%